The interaction between endothelin-1 and C-reactive protein and their impact on long-term prognosis after percutaneous coronary interventions - Catakoglu, Alp Burak; Aytekin, Vedat; Demiroglu, Cemsid; Aytekin, Saide (Archives of Medical Science, 2009)
Introduction: Previous studies have demonstrated unfavourable outcomes in coronary artery disease and percutaneous coronary intervention (PCI) patients with high endothelin-1 (ET-1) or high sensitivity C-reactive protein (hs-CRP) levels. The aim of our study was to investigate the impact of pre-procedural ET-1 and hs-CRP levels on major adverse coronary events (MACE) after PCI and to analyse a possible correlation between ET-1 and hs-CRP in this study population. Material and methods: Eighty consecutive PCI patients with a single de novo, non-occlusive coronary lesion were included. Blood samples were obtained immediately before the procedure. The study endpoint was the occurrence of MACE, which was defined as death (all causes), non-fatal myocardial infarction or repeat coronary revascularization (PCI or surgery). Results: At the end of the 24 months’ follow-up, 28 patients (35%) reached an end-point. We could not observe any correlation between ET-1 and hs-CRP in the overall patient group (r = 0.141, p = 0.213). Neither ET-1 nor hs-CRP levels were found to be predictive for MACE after PCI in multivariate analyses (p = 0.605 and 0.757 respectively). Conclusions: We could not demonstrate a relationship between pre-procedural ET-1 or hs-CRP levels and MACE at 24 months after successful PCI with single stent implantation to single de novo lesions. This study also could not show any correlation between ET-1 and hs-CRP levels in PCI patients.